Protection and Welfare of Orphans: "Relating the 1945 Constitution Article 34 Paragraph 1 with the Scope of Regional Government Based on the Theory of the Koran" - Maulana, Yofi Raja; Siregar, Muhammad Nuh (Academy of Education Journal, 2024)
This research discusses the implementation of the 1945 Constitution Article 34 Paragraph 1 in the policy of protecting orphans using a theoretical approach to the Koran. The research focus includes aspects of justice, compassion, social responsibility, social empowerment and the rights of orphans. Al-Qur'an theory is integrated to provide an ethical and moral basis for policy formation. Research findings show that holistic integration between the legal basis and the values of the Koran can optimize the protection of orphans. Alignment, empowerment and community participation are the keys to creating effective and meaningful policies. It is hoped that the results of this research can provide guidance for the development of policies for the protection of orphans that are better, fairer and based on Islamic values.